Physicochemical characterization of Dillenia indica fruits and exploration of extraction methods to obtain reducing compounds and pectin - Isabela A. Silva; Luana E. Carmo; Marília G. Pereira; Patricia Sinnecker; Aline A. Cavalari; Priscilla C. Veggi; Fabiana Perrechil (Applied Food Research)
Dillenia indica Linn. is an unconventional edible plant with numerous health benefits, including anti-diabetic, anti-inflammatory, and anticancer properties. Dillenia indica fruit, known as elephant apple, is rich in nutrients and bioactive compounds and is an excellent source of pectin, a polysaccharide extensively used in the food industry. Despite the potential of this plant, it has been little studied and is still under-explored for commercial purposes. This study aimed to explore methods for extracting total reducing compounds and pectin from Dillenia indica fruit. First, the extraction of reducing compounds was optimized by ultrasound-assisted method within an experimental design considering three variables: solvent-to-feed (S/F) ratio (10:1 – 30:1), ethanol-to-water ratio (0:100 – 100:0) and ultrasound amplitude (24 – 40 %). In the following step, kinetic curves at the optimized conditions were obtained for up to 16 min. The ultrasound-assisted method was then compared to mechanical stirring (100 rpm). In the last step, pectin was extracted, maintaining the same S/F ratio (30:1) and ethanol-to-water ratio (20:80), but using magnetic stirring, pH 2.0, and 80 ºC. Pure water at pH 2.0 was used as a solvent for comparison. In the ultrasound-assisted extraction, the optimal yield was achieved with an S/F ratio of 30:1, an ethanol-to-water ratio of 20:80, and an ultrasound amplitude of 24 %. In the kinetic curves, a higher reducing capacity was obtained at 8 min through mechanical stirring. The pectin extraction was more effective with pure water (12.1 %). However, the ethanol-water mixture promoted a similar amount of pectin (10.3 %) but with a considerably higher total reducing capacity (25.82 mg GAE/g for ethanol-water and 14.5 mg GAE/g for pure water). These results demonstrated that reducing compounds and pectin can be effectively extracted from Dillenia indica fruit, highlighting the potential of this fruit to produce valuable ingredients.